Caracterização molecular e laboratorial da talassemia beta e da interação hemoglobina s/talassemia beta - Silveira, Zama Messala Luna da (2010)
Beta thalassemia arises as a consequence of the reduction (β+, β++, βsilent) or absence (β0) of beta globin chain synthesis and results from a number of mechanisms that lead to genetic defects. The inheritance of beta thalassemia is characterized by the existence of heterozygous individuals, compound heterozygotes, homozygotes and those with coinheritance of beta thalassemia allele and other thalassemias and/or hemoglobin variants. The aim of this study was to perform molecular and laboratory characterization of beta thalassemia in heterozygous and homozygous individuals and in those with coinheritance of S beta thalassemia. A total of 48 individuals were included (35 heterozygotes, 4 homozygotes and 9 S beta thalessemia carriers) referred to the Integrated Laboratory of Clinical Analyses of the Federal University of Rio Grande do Norte (UFRN) and the Hematology Ambulatory Facility of the Dalton Barbosa Cunha Hemocenter (Hemonorte Natal, Brazil). Peripheral blood samples form each patient underwent the following laboratory examinations: erythrogram, hemoglobin electrophoresis at alkaline pH, measurements of Hb A2, Fetal Hb and serum ferritin. DNA was extracted using the illustra blood genomicPrep Mini Spin Kit and molecular characterization was performed by the PCR/RFLP technique, which involves digestion with specific restriction enzymes for IVS-1 nt 1 (G®A), IVS-1 nt 6 (T®C) and codon 39 (CAG®TAG) mutations. Of the 35 heterozygotes, 37.1% showed IVS-1 nt 6 mutation, 42.9% IVS-1 nt 1 and 20% were carriers of other mutations not identified by the technique used. The four homozygous patients presented with the IVS-1 nt 6 mutation, while 66.7% of the individuals with S beta thalassemia had the IVS-1 nt 1 mutation. Codon 39 was not detected in any of the patients investigated. Of the thallasemic alleles found, 40.4% were IVS- 1 nt 1, 40.4% IVS-1 nt 6 and 19.2% were not identified. Laboratory data showed that the heterozygotes exhibited microcytosis and hypochromia, evidenced by MCV ranging from 57 to 75fL and MCH from 15.9 to 23.6 pg. Hemoglobin A2 varied between 3.7 and 7.2%. The homogygotes also showed reduced MCV and MCH and elevated HbA2.. Comparison of laboratory data between heterozygous individuals with IVS-1 nt 1 and IVS-1 nt 6 mutations showed that heterozygotes for the IVS1-1 mutation had significantly lower mean MCV and MCH (p = 0.023 and 0.007, respectively) and significantly higher hemoglobin A2 (p < 0.001) when compared to heterozygotes for the IVS-1 nt 6 mutation. PCR/RFLP was useful in identifying the presence or absence of IVS-1 nt 6, IVS-1 nt 1 and codon 39 mutations in most of the patients investigated here. This is the first study conducted in the state of Rio Grande do Norte, Brazil aimed at identifying beta thalassemia mutations and represents an important contribution to the knowledge regarding the molecular profile of beta thalassemia in our country